Utopian science and empire : notes on the iberian background of Francis Bacon's project - Manzo, Silvia (2010)
This paper will explore Bacon's perceptions of the scientific connotations of the Spanish empire and his reception of early modern Iberian science. Its aim is to analyze the extent to which the Iberian background played a role in the making of Bacon's project of a utopian imperial science, by drawing attention to some particular cases: the reception of the Jesuits, the natural histories, the chronicles of discovery, and the evaluation of Columbus' voyages. It is shown that Bacon's relationship with Iberian themes and sources was explicit in a few cases (Acosta, Columbus, Inca Garcilaso, the Jesuit order), while at other times the relationship is more indirect and implicit (Fernández de Oviedo, López de Gomara, Martire, Ramusio, Benzoni, Fernández de Quirós). It is argued that early modern imperial Spain seems to have been assessed by Bacon as a model of a growing empire, an empire whose greatness relied heavily on the Jesuit order and the colonization of America. The paper concludes that the attentive observation of the Spanish empire as well as the acquaintance with the Jesuits and the Iberian chronicles must have inspired Bacon's project of science and his ideas on the articulation of science with empire. At the same time, other past and contemporary authors and traditions found their place in Bacon's program for the reform of learning. This eclectic blend underlying this project rather than depriving the end result of novelty, allows us to realize the new decisive contents Bacon added to the diverse ideas and practices he relied on.
Documento incorporado en 2019 en el marco del "Programa de becas de experiencia laboral" de la Biblioteca Profesor Guillermo Obiols para estudiantes de Bibliotecología, a partir de un procedimiento técnico de captura de datos desarrollado por el personal del IdIHCS.
Keywords: Francis Bacon; Iberian science; Empire; Chronicles of America; Jesuits; Bacon, Francis; Jesuitas; Colonialismo; Conquista de América